Lipid emulsions for parenteral nutrition in critical illness. (October 2015) - Boisramé-Helms, Julie; Toti, Florence; Hasselmann, Michel; Meziani, Ferhat
Abstract: Critical illness is a life-threatening multisystem process that can result in significant morbidity and mortality. In most patients, critical illness is preceded by a physiological deterioration, characterized by a catabolic state and intense metabolic changes, resulting in malnutrition and impaired immune functions. In this context, parenteral lipid emulsions may modulate inflammatory and immune reactions, depending on their fatty acid composition. These effects appear to be based on complex modifications in the composition and structure of cell membranes, through eicosanoid and cytokine synthesis and by modulation of gene expression. The pathophysiological mechanisms underlying these fatty acid-induced immune function alterations in critical ill patients are however complex and partially understood. Indeed, despite a very abundant literature, experimental and clinical data remain contradictory. The optimization of lipid emulsion composition thus represents a major challenge for clinical medicine, to adequately modulate the inflammatory pathways. In the present review, we first address the metabolic response to aggression, the effects of parenteral lipid emulsions on inflammation and immunity, and finally the controversial place of these lipid emulsions during critical illness. The analysis furthermore highlights the pathophysiological mechanisms underlying the differential effects of lipid emulsions and their potential for improving the handling of critically ill patients.